The Instructional Leadership Role of Principals in Developing Good Practices in Teaching & Learning Process in the Tamil Medium Schools of Puttalam District in Sri Lanka - Safeek, N.M.M.; Nawastheen, F.M. (South Eastern University of Sri Lanka, 2016)
The purpose of this study was to evaluate perception of school principals towards their instructional leadership roles in developing good practices in the teaching & learning process. For achieving this purpose, following research questions were also included: (i) what are the perception of principals on their instructional leadership roles? (ii) What is the perception of teachers & other academic staff towards on the instructional leadership role of principals? (iii) what are the best practices developed by performing instructional leadership roles of principals in the teaching & learning process? (iv) What are the differences in the instructional leadership role of principals towards students’ achievements based on their school types, qualifications, and experience? Population of the study was school principals and teachers from Tamil medium schools in Puttalam district in Sri Lanka. A mixed research method carried out with stratified probability sampling. 33 principals, 20 teachers and 10 academic officers were selected. Adopted Principal Instructional Manual Rating Scale (PIMRS) questionnaire was employed to collect data from principals and self-developed an interview schedule was used to collect data from teachers and academic officers. One way ANOVA and post-hoc methods were used for analyze the quantitative data. The results revealed that the principal of Puttalam district has a positive perception on their instructional leadership roles especially principals from 1C and Type 2 Schools were highly shown instructional leadership behavior and it was significantly related indirectly on students’ achievement. However, they showed low level of perceptions on class supervision and monitoring the students’ progress. The findings were suggested that the quality of instructional leadership roles of principals should be increased. and class supervision, monitoring students’ progress and learning climate should be developed for the best instructional practices.
Keywords: Instructional Leadership; Perceptions; Teaching and Learning Process; Students’ Achievements; Puttalam